Zastosowanie Internetu w działaniach marketingowych Zakładów Tłuszczowych "Kruszwica" - Pizło, Wojciech (Internet Use in Marketing Actions in the Fat Company "Kruszwica", 2005)
The paper presents the use of the Internet in marketing actions in the enterprise ZT "Kruszwica". The paper shows marketing strategy together with a strategy realized in the Internet. Problems of Internet marketing development are also presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 200-208